Effect of Pranayama on Anxiety Level of College Female Students - Pinkesh, Dr. Pramjeet Singh Ghuman, Om Prakash Bhadana (International Journal of Advanced Science and Technology, 2020)
The objective of the study was to investigate the impact of pranayama on anxiety levels among college female students. The study was conducted on 80 female college athletes aged between 18 to 21 years. Selected Two sets of subjects were created, each group having 40 numbers – one control and the other experimental group. In this present study, the researcher made an attempt to explore the impact of pranayama on anxiety level of college female student psychological depression. Anxiety stress scale i.e Depression, Anxiety and Stress (DASS) being propounded by Lovibond &S. Hand in 1995 was employed in order to conduct the study. There was an application of statistical tool i.e. paired t-test to draw inferences. The statistical findings: the experimental group that had done the pranayama training found out to be having lesser levels of anxiety as compared to the other group that did not do any pranayama. This ultimately led to the rejection of null Hypothesis as there was significant effect of pranayama on Anxiety (psychological variable)